The Importance of Stimulation of Fine Motor Development for Early Childhood - Aura Maharani; Nita Karomatunnisa; Nur Asy-Syifa Jamilah (Feelings: Journal of Counseling and Psychology, 2024)
This research is a literature study which aims to determine the importance of stimulating fine motor development for young children. The method used in this research is a qualitative descriptive research method with literature study. In this literature study research, researchers used various written sources such as articles, journals and documents that were relevant to the research in this study. From this research literature study, it can be concluded that by providing appropriate stimulation, fine motor development in early childhood can be achieved optimally. This will have a positive impact on various aspects of children's development, both from a cognitive, social and emotional perspective. Therefore, it is important for parents and teachers to realize the importance of stimulating fine motor development for young children and use appropriate methods to stimulate children's fine motor development.